2017
DOI: 10.15252/embj.201696035
|View full text |Cite
|
Sign up to set email alerts
|

Coactivators and general transcription factors have two distinct dynamic populations dependent on transcription

Abstract: SAGA and ATAC are two distinct chromatin modifying co‐activator complexes with distinct enzymatic activities involved in RNA polymerase II (Pol II) transcription regulation. To investigate the mobility of co‐activator complexes and general transcription factors in live‐cell nuclei, we performed imaging experiments based on photobleaching. SAGA and ATAC, but also two general transcription factors (TFIID and TFIIB), were highly dynamic, exhibiting mainly transient associations with chromatin, contrary to Pol II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 85 publications
(149 reference statements)
1
18
0
Order By: Relevance
“…This discrepancy could be explained by an inherent difficulty to ChIP the SAGA complex (HTM. Timmers, unpublished observations), which can be due to its very dynamic interaction with chromatin ( Vosnakis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy could be explained by an inherent difficulty to ChIP the SAGA complex (HTM. Timmers, unpublished observations), which can be due to its very dynamic interaction with chromatin ( Vosnakis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The above three groups of genes (evolved linked protein complex genes, linked protein complex genes, and unlinked protein complex genes) were constructed using stratified sampling so that their mean expression levels across tissues are not significantly different (see Methods). For comparison, we performed the same analysis but replaced H1 histones with TFIIB, a general transcription factor that is involved in the formation of the RNA polymerase II preinitiation complex and has a high diffusion rate [53]. The trends shown in Fig.…”
Section: Beneficial Linkage Of Genes Encoding Components Of the Same mentioning
confidence: 99%
“…5, D–F ), indicating that the observed Pol II cluster size shift reflected in vivo Pol II behavior changes after transcription inhibition. Using photobleaching techniques, it has been shown that, when transcription elongation is inhibited, total bound Pol II is released from the chromatin in general and becomes mobile ( Kimura et al, 2002 ; Hieda et al, 2005 ; Vosnakis et al, 2017 ). Thus, our results show that when transcription elongation is inhibited by Flavo the larger Pol II foci dissociate, because Pol II molecules are released from these sites and become mobile.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well established that the function of transcription factors and coactivator complexes involved in chromatin-dependent processes are tightly linked to their mobility and interactions with diverse posttranslational modifications (PTMs) in the nuclear environment ( Snapp et al, 2003 ; Kimura, 2005 ; Hager et al, 2009 ; Cisse et al, 2013 ; Vosnakis et al, 2017 ). Our current understanding of transcription regulation dynamics is often based on approaches, called fluorescence recovery after photobleaching and florescence loss in photobleaching, in which fluorescently tagged factors in the nucleus, or a whole cellular compartment, are bleached and the fluorescence redistribution is followed over time in live cells ( Kimura et al, 1999 , 2002 ; Dundr et al, 2002 ; Kimura, 2005 ; Gorski et al, 2008 ; van Royen et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%